DISTRIBUTION OF JOINT PROPERTY DUE TO ANNULMENT OF MARRIAGE DUE TO ONE OF THE SPOUSES CHANGING RELIGION - Putri, Devira Felisa; Erwinsyahbana, Tengku (Pena Cendekia Insani, 2026)
Religious conversion carried out by one of the couples in marriage has various legal consequences, especially in marriages that take place under Islamic law. One of the legal consequences that can arise is the annulment of marriage (fasakh) by the Religious Court because the legal requirements for marriage according to religious law are not met. The annulment of the marriage not only has an impact on the legal status of the husband and wife, but also has implications for the division of joint property obtained during the marriage bond. This study aims to analyze the legal consequences of marriage annulment because one of the couples changes religion and the mechanism of sharing joint property after the annulment of the marriage. The research method used is normative legal research with a regulatory approach and a conceptual approach. Law Number 1 of 1974 concerning Marriage and Compilation of Islamic Law. Thus, even if the marriage is declared null and void, the civil rights of the parties still receive legal protection.